Design of efficient metal-free organic dyes having an azacyclazine scaffold as the donor fragment for dye-sensitized solar cells - Biswas, Abul Kalam; Barik, Sunirmal; Sen, Anik; Das, Amitava; Ganguly, Bishwajit (Journal of Physical Chemistry C, 2014)
The energy conversion efficiency of dye-sensitized solar cells derived from organic dye molecules has seen immense interest recently. In this work, we report a series of organic donor molecules with enhanced energy conversion efficiency using ?-spacers and cyanoacrylic acid as an anchoring group (2-6). Density functional theory (DFT) and time-dependent DFT calculations of these molecules have been performed to examine their electronic structures and absorption spectra before and after binding to the semiconductor titanium dioxide surface. The computational results suggest that dyes 4 and 6 have a larger driving force (Delta G(inject) = -1.66 and -1.80 eV, respectively) and light-harvesting efficiency (LHE = 0.99) in the series of donor molecules studied. Thus, these dyes should possess a larger short-circuit photocurrent density (J(sc)) compared to the other examined dyes. The reported Delta G(inject) (-1.62 eV) and LHE (0.98) for compound 1, calculated with the same level of theory, were lower than those of the designed 4 and 6 dyes. Furthermore, the DFT calculations showed that the open-circuit photovoltage (V-oc) is improved with the vertical dipole moment and number of photoinjected electrons for 4 and 6. Dyes 4 and 6 are expected to exhibit high solar-energy-to-electricity conversion.

Does the position of the electron-donating nitrogen atom in the ring system influence the efficiency of a dye-sensitized solar cell? A computational study - Biswas, Abul Kalam; Barik, Sunirmal; Das, Amitava; Ganguly, Bishwajit (Journal of Molecular Modeling, 2016)
We have reported a number of new metal-free organic dyes (2-6) that have cyclic asymmetric benzotripyrrole derivatives as donor groups with peripheral nitrogen atoms in the ring, fluorine and thiophene groups as pi-spacers, and a cyanoacrylic acid acceptor group. Density functional theory (DFT) and time-dependent DFT (TD-DFT) calculations were employed to examine the influence of the position of the donor nitrogen atom and pi-conjugation on solar cell performance. The calculated electron-injection driving force (Delta G(inject)), electron-regeneration driving force (Delta G(regen)), light-harvesting efficiency (LHE), dipole moment (mu(normal)), and number of electrons transferred (Delta q) indicate that dyes 3, 4, and 6 have significantly higher efficiencies than reference dye 1, which exhibits high efficiency. We also extended our comparison to some other reported dyes, 7-9, which have a donor nitrogen atom in the middle of the ring system. The computed results suggest that dye 6 possesses a higher incident photon to current conversion efficiency (IPCE) than reported dyes 7-9. Thus, the use of donor groups with peripheral nitrogen atoms appears to lead to more efficient dyes than those in which the nitrogen atom is present in the middle of the donor ring system.
Keywords: DFT; Dye-sensitized solar cells; Organic dyes; Position effect; TD-DFT